E-Learning of Foreign Languages at the University of Dubrovnik, Experiences and Attitudes of Users - Režić Tolj, Zrinka; Lucijana Leoni; Jasenka Maslek (European Journal of Social Science Education and Research, 2016)
At the time of computerization and digitization of modern society the use of modern technology in education is logical and natural. At the University of Dubrovnik, e-learning was implemented in 2005. Since then the number of users of the platform for e-learning is constantly increasing. The goal of the research, conducted at the beginning of 2016 at the University of Dubrovnik, using two different but similarly structured questionnaires, among teachers and their students, was to determine the degree and manner of use of Moodle platform in a hybrid language teaching (at the University of Dubrovnik), and to examine, among users of e-learning, the use of various possibilities that this system of modern way of teaching offers, as well as their attitudes on the acceptance of e-learning in foreign language teaching and learning. Research shows that the use of e-learning technology has many advantages for students but also for teachers, although it requires a lot more investment and effort from them. The attitudes on the use of modern ways of e-teaching languages are generally positive and positively affect its increasing use.
Keywords: language teaching, e-technology, e-learning, hybrid language teaching